Bacterial Gut Microbiota and Infections During Early Childhood - George, Sergio; Aguilera, Ximena; Gallardo, Pablo; Farfán, Mauricio; Lucero, Yalda; Torres, Juan Pablo; Vidal, Roberto; O’Ryan, Miguel (Frontiers in Microbiology, 2022)
Gut microbiota composition during the first years of life is variable, dynamic and influenced by both prenatal and postnatal factors, such as maternal antibiotics administered during labor, delivery mode, maternal diet, breastfeeding, and/or antibiotic consumption during infancy. Furthermore, the microbiota displays bidirectional interactions with infectious agents, either through direct microbiota-microorganism interactions or indirectly through various stimuli of the host immune system. Here we review these interactions during childhood until 5 years of life, focusing on bacterial microbiota, the most common gastrointestinal and respiratory infections and two well characterized gastrointestinal diseases related to dysbiosis (necrotizing enterocolitis and Clostridioides difficile infection). To date, most peer-reviewed studies on the bacterial microbiota in childhood have been cross-sectional and have reported patterns of gut dysbiosis during infections as compared to healthy controls; prospective studies suggest that most children progressively return to a “healthy microbiota status” following infection. Animal models and/or studies focusing on specific preventive and therapeutic interventions, such as probiotic administration and fecal transplantation, support the role of the bacterial gut microbiota in modulating both enteric and respiratory infections. A more in depth understanding of the mechanisms involved in the establishment and maintenance of the early bacterial microbiota, focusing on specific components of the microbiota-immunity-infectious agent axis is necessary in order to better define potential preventive or therapeutic tools against significant infections in children.